Pengembangan Media Leaflet Berbasis SSI (Socio-Scientific Issues) Sebagai Media Pembelajaran Siswa SMA pada Materi Sistem Peredaran Darah di Kelas XI - Anggita Anggeraini Harahap; Efrida Pima Sari Tambunan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to Develop an instructional medium in the form of a leaflet based on Socio-Scientific Issues (SSI) for the Human Circulatory System topic in Grade XI senior high school students. The Development process employed the 4D model (Define, Design, Develop, and Disseminate). The Define stage involved a needs analysis through interviews and observations, revealing that learning remained textbook-centered and lacked connections to social issues. The Design stage produced a tri-fold leaflet featuring communicative language and supporting illustrations. The product was then validated by media and material experts during the Develop stage and subsequently tested on students. The results show that media and material validation scores were both 90% (categorized as highly feasible). Teacher responses reached 90.76%, and student responses reached 85%, indicating that the leaflet is attractive, easy to use, and supports conceptual understanding. Furthermore, students' learning interest increased, with an average score of 95.44% (very high category). In conclusion, the SSI-based leaflet is considered practical, effective, and feasible to be used as a teaching material that supports contextual and meaningful biology learning. Keywords: Leaflet, Learning Interest, Learning Media, SSI (Socio-Scientific Issues)